Adverse Effects of Transaction Costs in East European Economies - Todorova, Tamara (Organizations and Markets in Emerging Economies, 2011)
Abstract. At a given level of technology the gross aggregate production function lies above the net aggregate production function where the difference represents the aggregate transaction costs in the economy. Transitional economies facing serious institutional impediments to creating a smoothly functioning market mechanism are faced with sizable transaction costs. We use a net production function model enhanced by Furubotn and Richter and apply it conceptually to the case of transitional economies. We find that at a particular level of a community isoprofit line much less output will be supplied compared to developed market economies with mature market institutions. The aim of the paper is to trace the falling output and the deep structural problems of East European economies to the effect of transaction costs and institutional building. The more rapidly transaction costs grow, the less the firms would be willing to pay for inputs. Furthermore, we find that certain markets tend to disappear in emerging economies due to the adverse effects of transaction costs. As a safeguard to precontractual opportunism and prevention to ex post transaction costs, ex ante transaction costs would play a more vital role in East European societies.